ASSESSING THE UNIVERSAL DESIGN OF PEDESTRIAN FACILITIES IN THE CENTRAL AREA OF CILEGON CITY - Sari, Attiya Arrum; Nilma, Weni Laysa (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2024)
This research examines the application of universal design to pedestrian facilities in the Cilegon City. It uses descriptive qualitative methods where the data are gathered from observation. The findings reveal that some issues include uneven sidewalk widths, misaligned pedestrian routes, and improper slopes at crossings, compounded by obstacles such as street vendors, damaged drainage covers, and uneven pavement materials. While elements like seating and guiding paths have been considered, their implementation does not meet necessary standards. The lack of bollards, safety rails, and speed control devices compromises pedestrian safety, especially in high-traffic areas. The study also highlights challenges for individuals with disabilities, including difficulties faced by wheelchair users and the elderly due to uneven surfaces, discontinuities in guiding paths, and insufficient resting areas. Overall, improvements in accessibility, safety, and infrastructure continuity are recommended to ensure that Cilegon City’s pedestrian facilities are fully inclusive and usable by all, regardless of physical ability.